The Rif GTPase regulates cytoskeletal signaling from plexinA4 to promote neurite retraction. (17th March 2015) - Fan, Lifei; Yan, Huijuan; Pellegrin, Stephanie; Morigen,; Mellor, Harry
Graphical abstract: Highlights: Rif interacts with the Rho GTPases activator FARP1. Rif interacts with the semaphorin receptor plexin A4. Binding of Rif to plexin A4 controls its association with FARP1. Binding of Rif to FARP1 regulates activation of RhoA. This regulation of the plexin A4/FARP1 complex by Rif controls neurite retraction in response to Sema6A. Abstract: The small GTPase Rif is required for the early stages of dendritic spine formation in neurons, acting through the formin mDia2 to control actin polymerization. Rif is expressed at high levels in the brain, suggesting broader roles in neuronal function. We screened a yeast two-hybrid cDNA library to identify additional binding partners for Rif of potential relevance to neuronal function. We found that Rif interacts with FARP1, a neuronal activator of the RhoA GTPase. We show that Rif has two separate roles in FARP1 regulation–in controlling its association with plexinA4, and in releasing active RhoA from a plexinA4/FARP1 complex. The regulation of FARP1 by Rif promotes neurite retraction in cells stimulated with the semaphorin Sema6A.